Preparation and Evaluation of High-Nutritional Value Biscuits from Whole Wheat flour, Carrot and Whey Protein Powder - Amira, E. Abd El Gwad; Alshaimaa, M. Hamouda; Gamal, S. El-Hadidy (Food Technology Research Journal)
Biscuits are among the most popular ready-to-eat foods globally, valued for their low cost and long shelf life. They are not only a convenient snack but also a versatile product that can be enriched to improve nutritional content, meet dietary needs, and address certain health concerns. This study aimed to develop nutrient-enriched biscuits by fortifying them with whole wheat flour (WWF), whey protein concentrate (WPC), and carrot powder (CP) in varying proportions: blend 1 (control, 100% WF), blend 2 (95% WWF + 5% CP), blend 3 (85% WWF + 5% CP + 10% WPC), blend 4 (80% WWF + 5% CP + 15% WPC), and blend 5 (75% WWF + 5% CP + 20% WPC). The results showed that WPC was high in crude protein and calcium and provided essential amino acids such as lysine and leucine. WWF, on the other hand, excelled in non-essential amino acids like glutamic acid and proline, while CP contributed high fiber and mineral content, including a notable amount of iron. Texture analysis indicated increased hardness and fracturability with WPC fortification. Sensory evaluation revealed that blends 3 and 4, which incorporated WPC, improved taste and overall acceptability. However, excessive WPC in blend 5 led to undesirable changes in texture and color. These findings suggest that WWF, WPC, and CP offer complementary nutritional profiles, which can enhance the nutritional value and sensory qualities of biscuits, resulting in a functional food product with potential health benefits.